An analysis of the gap between accounting depreciation and tax capital allowance in Malaysia - Yussof, Salwa Hana; Mohd. Isa, Khadijah; Mohdali, Raihana (2014)
Malaysian tax system includes a tax depreciation rule separate from accounting depreciation. This paper is to compares and contrasts the accounting treatment of depreciation and the tax treatment of capital allowance. The gap between the accounting and tax is resulted from different definitions of capital expenditure and qualifying asset and also different deduction rate and useful life used in calculating depreciation. This paper proposes the government to revise the current capital allowance system.